2018
DOI: 10.1111/2047-3095.12210
|View full text |Cite
|
Sign up to set email alerts
|

Possible Solutions as a Concept in Behavior Change Interventions

Abstract: As nurses engage in behavior change interventions, supporting patients and families in problem-solving will optimize health outcomes and transform clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…While general MA intervention research has identified, compared, and improved health outcomes in other populations, women undergoing fertility treatment have not been the population of focus although background factors such as age, race, education, income, and health insurance status have influenced medication-taking behaviors in other patient populations (20-24). Thus, examining women’s perceptions about oral MA while taking fertility medications addresses an important knowledge gap in reproduction science research which is pivotal to determining if solutions are needed to assist women to overcome these behaviors ( 25 ). The purpose of this study was to identify women’s perceived barriers to and facilitators of oral MA during ovarian stimulation while documenting their medication-taking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…While general MA intervention research has identified, compared, and improved health outcomes in other populations, women undergoing fertility treatment have not been the population of focus although background factors such as age, race, education, income, and health insurance status have influenced medication-taking behaviors in other patient populations (20-24). Thus, examining women’s perceptions about oral MA while taking fertility medications addresses an important knowledge gap in reproduction science research which is pivotal to determining if solutions are needed to assist women to overcome these behaviors ( 25 ). The purpose of this study was to identify women’s perceived barriers to and facilitators of oral MA during ovarian stimulation while documenting their medication-taking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…También corrobora que las intervenciones implantadas para resolver o mitigar los problemas de falta de conocimiento y manejo ineficaz de la salud van dirigidas principalmente a la mejora del control glucémico, tal y como la literatura acerca del tema (Minthorn & Lunney, 2012), no teniéndose en cuenta otros factores o parámetros. Además, las enfermeras comunitarias dada su autonomía de gestión de procesos están en una posición única para implementar intervenciones de cambio de comportamiento, permitiendo que el paciente autogenere soluciones para alcanzar resultados específicos de salud (Mahoney, 2019).…”
unclassified